Assessment of Mortality Rate Using qSOFA Score among Patients with Sepsis outside the Intensive Care Unit (ICU) in a Tertiary Care Hospital - Muhammad Fahad Iqbal; Karim Ullah Makki (Pakistan Journal of Health Sciences, 2026)
Sepsis is a severe condition associated with a high risk of death. The Quick Sequential Organ Failure Assessment (qSOFA) score is an easy bedside instrument for mortality prediction. Objective: This study aims to assess the mortality rate in patients with sepsis having a qSOFA score of 2 or more. Methods: This cross-sectional research was done for 6 months, from July 2025 to December 2025, among 196 patients at Liaquat National Hospital Karachi. The sample comprised patients with sepsis, not admitted to the ICU, and aged between 18 and 75 years, with qSOFA assessed at admission, and followed until discharge or death. A qSOFA score of 2 was determined to be a predictive value of mortality. The statistical analysis was done in SPSS version 25.0; stratification and the Chi-square or Fisher’s exact test were. A p-value < 0.05 was considered statistically significant. Results: 196 non-ICU sepsis patients were included (mean age 55.9 ± 17.9 years; 55.1% male). The median qSOFA score was 2, with 104 (53.1%) patients having qSOFA ≥2. In-hospital mortality occurred in 97 (49.5%) patients. qSOFA ≥2 was significantly associated with older age, male gender, rural residence, hypertension, diabetes, anemia, hypotension, tachypnea, and GCS